Cooperative Governance of Complex Public-Private Partnership Program: Case Study of Characteristic Town Program - Zhen Chen (Advances in Civil Engineering)
PPP program is characterized by great organizational complexity, complicated communication network, and high coordination cost, which lead governance problems to be more complex than usual construction projects. Investigating 49 stakeholders of the D characteristic town construction program, the author constructs the work interaction network and supervision network of characteristic town PPP program based on organizational relationship. Through the calculation and comparison of network parameters, the network problems were analyzed, and the governance improvement scheme was proposed. The results show that, during the construction phase of the PPP program, (1) the SPV is still the core stakeholders; (2) the PPP program supervison belongs to hierarchical supervision characteristics and (3) the government regulators and loan institutions have limited influences on the program but they can restrict the SPV by strengthening supervision with subprogram stakeholders.